Keffiyeh trend on social media as a form of solidarity for Palestine - Zulaihah, Sitti (Digital Theory, Culture & Society, 2023)
This study explores the widespread adoption of the keffiyeh trend within the global community, including Indonesia, as a form of solidarity in support of Palestine. The surge in the keffiyeh trend intensified following Israel's forceful assault on Palestine, purportedly in response to Hamas' actions on October 7, 2023.Employing virtual ethnography through the analysis of social media content, the research delves into the historical context of the keffiyeh among Arabs. Known by different names across various Arab nations, such as kufiyah, gutrah in Saudi Arabia, shemag in Iraq, and keffiyeh in Palestine, this head-to-neck covering initially served as protection for village workers during outdoor activities. In the 1980s, the keffiyeh underwent a transformation into a fashion accessory, gaining popularity among young individuals with a bohemian style in New York. Notably, major global brands like Balenciaga and Louis Vuitton even incorporated keffiyeh motifs into their products. Despite its fading significance, the keffiyeh experienced a resurgence as a symbol of solidarity during global demonstrations and actions defending Palestine following Israel's renewed attacks. Participants in the Palestine Defense March prominently featured the keffiyeh, sharing images on social media platforms, notably Instagram, leading to a resurgence of the keffiyeh trend within the wider community.